FAKTOR YANG MELATARBELAKANGI UNMET NEED DI DUSUN JETAK DESA JASEM KECAMATAN NGORO KABUPATEN MOJOKERTO - Ifa Roifah (Bahasa Indonesia, 2016)
This study is based on the high level of unmet need in Indonesia. The high level of unmet need for spacing found among young women is less than 30 years old and a high level of unmet need for an end to the group of women are elderly and have a number of children as expected. This study aims to determine the factors behind unmet need in Jetak Jasem Village Ngoro District Mojokerto Regency. This study was descriptive. The populations in this study were all EFA that do not use family planning in Jetak Jasem Village Ngoro District Mojokerto Regency as many as 33 EFA. Sampling of this research is total sampling. The variables in this study were age, income, education, occupation, and number of children. The instrument used was a questionnaire. The results suggest that the age factor underlying the unmet need in Jetak Jasem Village Ngoro District Mojokerto Regency almost all respondents aged over 35 years, most of the income is less than or equal UMK, basic education, not working, and has two children. This suggests that the dominant factor behind the unmet need is the age factor. EFA did not use birth control due to feel old age, number of side effects that may arise as a result of birth control, forbidden by the husband to use birth control, the myth of the limit on the number of children that can be owned by the mother, and the herbal drink to not get pregnant.